Pilot participatory impact assessment (PPIA) of rural roads on rural poverty
The Participatory Policy Impact Assessment (PPIA) of rural roads on rural poverty is the first of its kind to be carried out in Bhutan. It is important to note that this was a pilot exercise, limited in coverage and scope, and conducted with a number of constraints and methodological shortcomings.